Malaysia's manufacturing landscape: Current challenges and production strategies - Nor Anija, Jalaludin; Amirul Syafiq, Sadun; Chulakit, Saranjuu; Hairulazwan, Hashim; Suziana, Ahmad; Nur Aminah, Sabarudin; Muhammad Ashraf, Fauzi; Wang, Zhiwen (Penerbit Akademia Baru, 2024)
Manufacturing is a complex industry where various methods, tools and labour come together to produce large-scale products. Each product and industry have its unique systems, layouts and procedures. Understanding these intricacies is vital for efficiency, product quality and competitiveness among the industries. This paper aims to explore the basics of the local manufacturing sector, the different production processes used and common problems on the manufacturing floor. In a November 2022 survey with about 56 participants in Malaysia, data were collected on how each of the participants' industries operated, along with some common problems. Human, machine and system issues were identified as common concerns among the industries. Surprisingly, despite the rise of automation and Industry 4.0, 10% of production lines still rely entirely on manual labour and 80.4% are semi-automated, highlighting a continued dependence on human labour for various tasks, even in today's technological landscape.